2022
DOI: 10.1073/pnas.2116518119
|View full text |Cite
|
Sign up to set email alerts
|

Measuring infectious SARS-CoV-2 in clinical samples reveals a higher viral titer:RNA ratio for Delta and Epsilon vs. Alpha variants

Abstract: Novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants pose a challenge to controlling the COVID-19 pandemic. Previous studies indicate that clinical samples collected from individuals infected with the Delta variant may contain higher levels of RNA than previous variants, but the relationship between levels of viral RNA and infectious virus for individual variants is unknown. We measured infectious viral titer (using a microfocus-forming assay) and total and subgenomic viral RNA levels (u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 14 publications
7
32
0
Order By: Relevance
“…Previous studies in clinical settings have shown that viral genome of certain SARS-CoV-2 variants is shed at higher levels than for other variants. This increased shedding in part has been suggested to contribute to in the increased spread of these variants [19]. However, .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in clinical settings have shown that viral genome of certain SARS-CoV-2 variants is shed at higher levels than for other variants. This increased shedding in part has been suggested to contribute to in the increased spread of these variants [19]. However, .…”
Section: Discussionmentioning
confidence: 99%
“…Following the identification of SARS-CoV-2 as the cause of coronavirus disease-2019 (COVID- 19), the virus has spread rapidly throughout the world. Since its emergence, viral genomic sequence analysis has allowed tracking of the emergence of SARS-CoV-2 variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These guidelines were initially framed based on contact tracing studies and laboratory studies that looked at culturable active viruses from 2020, which showed less than 5% risk for transmission at the late stage (23)(24)(25). Even though the Delta variant emerged to be more virulent and transmissible during the second wave in India and subsequently in other countries, the viral shedding dynamics of the infectious virus have just started emerging (9,(26)(27)(28)(29). One study that looked at infectious viruses upto15 days showed that infectious viral shedding is longer for the Delta than non-Delta infections (29).…”
Section: Transmission Risk Continues To Remain High In a Subset Of In...mentioning
confidence: 99%
“…Delta had substantially higher infectivity than Alpha based on the number of infectious units per quantity of viral E-gene RNA (5.9-fold increase; p < 0.0001) or subgenomic E RNA (14.3-fold increase; p < 0.0001) in clinical specimens identified as SARS-CoV-2-positive at the University of Washington Virology Laboratory between March and August 2021 in the United States [262].…”
Section: Viral Loadmentioning
confidence: 88%